2014
DOI: 10.3402/qhw.v9.23517
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of in-group contact through physical activity involvement for health and well-being among Korean immigrants

Abstract: This qualitative study is designed to examine the benefits of physical activity involvement with members of the same ethnic group. For this study, Korean immigrants who were members of Korean physical activity clubs such as badminton and tennis were selected as participants. Using a constructive grounded theory methodology, three themes were identified as benefits of physical activity involvement: (1) the experience of psychological well-being, (2) the creation of a unique cultural world, and (3) the facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
7
20
0
Order By: Relevance
“…Through this research, it has been suggested that serious leisure experience helps to aid health enhancements in the lives of Korean middle-aged women (Kim, Heo, & Kim, 2014 ). Dance experiences, like line dancing especially, provide middle-aged women with psychological, physical, and social benefits.…”
Section: Discussionmentioning
confidence: 95%
“…Through this research, it has been suggested that serious leisure experience helps to aid health enhancements in the lives of Korean middle-aged women (Kim, Heo, & Kim, 2014 ). Dance experiences, like line dancing especially, provide middle-aged women with psychological, physical, and social benefits.…”
Section: Discussionmentioning
confidence: 95%
“…According to Kim, Heo, & Kim, 2014 study, Korean immigrants organized their own sports club in which the members had the same ethnic identities and, as a result, they experienced psychological well-being and created their unique cultural world in a context of sports. The finding of this study is consistent with this idea that older Korean immigrants gained various social, cultural, and psychological benefits by engaging in leisure activities with other Korean immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a qualitative approach seems to be the most appropriate to explore lived experiences and health-related benefits (e.g., Kim, Heo, & Kim, 2014; Kim, Kim, Han, & Chin, 2015). For this study, interpretative phenomenological analysis (IPA) was used for detailed structural analysis of the interviews, as it aims to explore meanings of particular experiences (Smith, Flowers, & Larkin, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Although an increasing number of studies in sports and serious leisure have been conducted, few studies have investigated involvement in sports that are related to serious leisure—from immigrant perspectives. However, several studies have revealed that acculturation is positively associated with involvement in sports and physical activities among Asian immigrants (Kim et al, 2014 ; Lee, Sobal, & Frongillo, 2000 ). Furthermore, Lee et al ( 2011 ) provided evidence that Korean immigrants who engaged in serious leisure through basketball and soccer games with members of different racial groups came to embrace different cultural values and exhibited enhanced self-identification.…”
Section: Serious Involvement In Sportsmentioning
confidence: 99%
“…Kim, Heo, and Kim ( 2014 ) investigated a group of Korean immigrants who organized their own sports club with in-group members and maintained cultural identification and membership. They suggested that immigrants possessed in-group membership—and that as part of sports clubs, they may express serious involvement in certain recreational activities.…”
mentioning
confidence: 99%